Impact of the COVID-19 pandemic on sports and exercise - Ashley Ying-Ying Wong; Samuel Ka-Kin Ling; Lobo Hung-Tak Louie; George Ying-Kan Law; Raymond Chi-Hung So; Daniel Chi-Wo Lee; Forrest Chung-Fai Yau; Patrick Shu-Hang Yung (Elsevier, 2020)
Background: COVID-19 is a droplet-transmitted potentially fatal coronavirus pandemic affecting the world in 2020. The WHO recommended social distancing and human-to-human contact was discouraged to control the transmission. It has put many countries in a state of lockdown and sporting events (including the 2020 Olympics) have been affected. Participation in sports and exercise, typically regarded as healthy activities, were also debated. The local professional football leagues, governed by the Hong Kong Football Association, ultimately postponed all matches after much deliberation on the transmission risk for the spectators and on-field players. Large spectating crowds are well-known to be infectious hazards, but the infection risk for on-field players is less recognized. Aside from watching professionals exercise, many people opted to hike in the countryside during the weekends to avoid city crowds. This led to a widespread discussion on the issue of wearing a facemask during outdoor activities. Methods: A small sample of video footage of professional football players were analysed to track each players' time of close body contact and frequency of infection-risky behaviours to investigate the risk of virus transmission during football games.To investigate the physiological effect of wearing a facemask during exercise, we conducted a controlled laboratory, within-subject, repeated measures study of 23 healthy volunteers of various sporting backgrounds. They underwent graded treadmill walking at 4 km per hour for 6 min with and without wearing a surgical mask in a randomized order with sufficient resting time in between trials. The heart rate and the rate of perceived exertion (RPE) were recorded. Results: In a 90 min match, the average duration of close contact between professional football players was 19 min and each player performed an average of 52 episodes of infection-risky behaviours. The heart rate and RPE of subjects wearing a facemask was 128 beats per minute and 12.7 respectively. In those without a facemask, the results were a heart rate of 124 beats per minute and a RPE of 10.8. Conclusion: This suggests that the infection risk was high for the players, even without spectators. The laboratory study to investigate the physiological effect of wearing a facemask found that it significantly elevated heart rate and perceived exertion. Those participating in exercise need to be aware that facemasks increase the physiological burden of the body, especially in those with multiple underlying comorbidities. Elite athletes, especially those training for the upcoming Olympics, need to balance and reschedule their training regime to balance the risk of deconditioning versus the risk of infection. The multiple infection-control measures imposed by the Hong Kong national team training centre was highlighted to help strike this balance. Amidst a global pandemic affecting millions; staying active is good, but staying safe is paramount.